2002
DOI: 10.1038/sj.bdj.4801496
|View full text |Cite
|
Sign up to set email alerts
|

The intra- and inter-examiner reliability of quantitative light-induced fluorescence (QLF) analyses

Abstract: Objective To assess the reliability of the analysis stage of quantitative light-induced fluorescence (QLF). The QLF analysis involves subjective input from the user and this study examines the influence of this on the reproducibility of the QLF data. Method QLF images were taken of 20 human molar teeth that had been previously subjected to a demineralising solution (phosphoric acid 37%) to create artificial white spot lesions on their buccal surfaces. Following examination of the images, 16 were chosen to repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…The fl uorescence device showed good reproducibility whether it was operated by an experienced or less experienced investigator. Pretty et al 26 showed in a study using the QLF that an examiner novice to the technique demonstrated differences in intra-examiner reliability compared with other examiners with more training. They recommend that novices to the technique should be trained before they analyze experimental data.…”
Section: Discussionmentioning
confidence: 98%
“…The fl uorescence device showed good reproducibility whether it was operated by an experienced or less experienced investigator. Pretty et al 26 showed in a study using the QLF that an examiner novice to the technique demonstrated differences in intra-examiner reliability compared with other examiners with more training. They recommend that novices to the technique should be trained before they analyze experimental data.…”
Section: Discussionmentioning
confidence: 98%
“…20 It is reasonable to extrapolate this to stain assessments as the mechanism for stain detection is similar.…”
Section: Discussionmentioning
confidence: 98%
“…21 Sixteen teeth with lesions of varying severity were analysed by 10 examiners on three occasions. Both intra-and inter-examiner agreement was good, with few significant differences in DQ being found.…”
Section: Studies Using Qlfmentioning
confidence: 99%